Ferroelastic-switching-driven large shear strain and piezoelectricity in a hybrid ferroelectric - Hu, Yuzhong (2021)
Materials that can produce large controllable strains are widely used in shape memory devices, actuators and sensors1,2, and great efforts have been made to improve the strain output3-6. Among them, ferroelastic transitions underpin giant reversible strains in electrically driven ferroelectrics or piezoelectrics and thermally or magnetically driven shape memory alloys7,8. However, large-strain ferroelastic switching in conventional ferroelectrics is very challenging, while magnetic and thermal controls are not desirable for practical applications. Here we demonstrate a large shear strain of up to 21.5% in a hybrid ferroelectric, C6H5N(CH3)3CdCl3, which is two orders of magnitude greater than that in conventional ferroelectric polymers and oxides. It is achieved by inorganic bond switching and facilitated by structural confinement of the large organic moieties, which prevents undesired 180° polarization switching. Furthermore, Br substitution can soften the bonds, allowing a sizable shear piezoelectric coefficient (d35 ≈ 4,830 pm V-1) at the Br-rich end of the solid solution, C6H5N(CH3)3CdBr3xCl3(1-x). The electromechanical properties of these compounds suggest their potential in lightweight and high-energy-density devices, and the strategy described here could inspire the development of next-generation piezoelectrics and electroactive materials based on hybrid ferroelectrics.